Novel improvement of surface roughness for AA6020 using AlTiN coated HSS tool in comparison with uncoated HSS tool using surface roughness tester. (Journal of Pharmaceutical Negative Results, 2022)
Aim: The Main motive of this research is to detect surface roughness using surface roughness tester and analyse the enhancement of surface roughness for AA6020 using AlTiN coated HSS tool and compare the results with uncoated HSS tool.Materials and Methods: In this investigation, AA6020 of length 20mm and diameter 25mm is used. There are 2 groups in this research, the experimental group which is the AA6020 samples drilled with AlTiN coated HSS tool and control group which is the AA6020 samples drilled with uncoated HSS tool. According to the calculation of G power, the sample size is derived to be 20 per group which makes the total sample size to be 40. The surface roughness test is carried out according to the ASTM standards.Results: An analysis of the results of surface roughness, it is observed that the average surface roughness for experimental group(AA6020 drilled with AlTiN coated HSS drill) is 1.36065μm. and for control group(AA6020 drilled with uncoated HSS drill) is 2.05065μm . On comparison of the results using ANOVA test f/or both the groups, it is noted that there is a significant decrease in surface roughness in the experimental group with significance level of 0.00 (P<0.05).Conclusion: Within the limitations of this study, we can conclude that AA6020 drilled with AlTiN coated HSS drill gives better results for surface roughness than AA6020 drilled with uncoated HSS drill.